INTERMITTENT DIPLOPIA IN CHORDOMA - (:unkn) unknown (AMER SOC CONTEMPORARY OPHTHALMOLOGY, 1994)
The symptoms and findings of three patients with clivus chordomas who had episodes of intermittent diplopia are presented. The causes of intermittent diplopia are reviewed, and the possible mechanisms of this symptom in chordomas are discussed.